Targeting macrophage liver X receptors by hydrogel‐encapsulated T0901317 reduces atherosclerosis without effect on hepatic lipogenesis. (23rd February 2021) - Ma, Chuanrui; Feng, Ke; Yang, Xiaoxiao; Yang, Zhimou; Wang, Zhongyan; Shang, Yuna; Fan, Guanwei; Liu, Lipei; Yang, Shu; Li, Xiaoju; Han, Jihong; Duan, Yajun; et al.
Abstract : Background and Purpose: Targeting macrophage but not hepatocyte liver X receptors (LXRs) can reduce atherosclerosis without effect on hepatic lipogenesis. In this study, we encapsulated LXR ligands with D‐Nap‐GFFY to form a nanofibre hydrogel (D‐Nap‐GFFY‐T0901317 or GFFY‐T0901317) and determined its effect on atherosclerosis, hepatic lipogenesis and the underlying mechanisms involved. Experimental Approach: D‐Nap‐GFFY‐T0901317 was subcutaneously injected to proatherogenic diet‐fed apoE‐deficient ( Apoe −/− ) mice, followed by determination of the development of atherosclerosis, liver steatosis and the involved mechanisms, with comparison of T0901317 oral administration. Key Results: Subcutaneous injection of D‐Nap‐GFFY‐T0901317 to Apoe −/− mice inhibited atherosclerosis at a comparable level as T0901317 oral administration without effect on hepatic lipogenesis. More importantly, D‐Nap‐GFFY‐T0901317 regressed the advanced lesions. In arterial wall, D‐Nap‐GFFY‐T0901317 reduced macrophage/foam cells, necrotic cores and calcification and increased collagen content. It activated expression of ABCA1/G1 and smooth muscle α‐actin, while inhibiting expression of intracellular adhesion molecule 1 (ICAM‐1) and vascular cell adhesion molecule 1 (VCAM‐1). D‐Nap‐GFFY‐T0901317 also reduced serum pro‐inflammatory cytokines and facilitated Kupffer cell M2 polarization. Mechanistically, D‐Nap‐GFFY‐T0901317 was selectively taken up by macrophages but not hepatocytes, resulting in activation of macrophage ABCA1/G1 expression, while having no effect on lipogenic genes in hepatocytes. Moreover, the selective uptake of D‐Nap‐GFFY‐T0901317 by macrophages was mainly completed in a scavenger receptor class A‐dependent manner. Conclusion and Implications: Our study demonstrates that D‐Nap‐GFFY‐T0901317 reduces atherosclerosis without effect on hepatic lipogenesis by targeting macrophage LXRs selectively, indicating its potential application for atherosclerosis treatment.